Helicopter Noise And Noise Abatement Procedures - Borivoj Galović; Doris Novak; Tomislav Kaštelan (Promet - Traffic&Transportation, 1970)
The helicopter generated noise at and around the airports islower than the noise generated by aeroplanes, since their numberof operations, i. e. the number of takeoffs and landings ismuch lower than the takeoffs and landings of the aeroplanes.Out of some hundred operations a day, helicopters participatewith approximately 15%, but the very impact of noise is by nomeans negligible, since the number of helicopter flights aboveurban areas is constantly increasing.This paper attempts to analyse this phenomenon and thetype of helicopter generated noise, its negative impacts, to explainthe flight procedures and the operative procedures duringtakeoff, landing and overflight of helicopters in operations inthe vicinity and outside airports, as well as the methods of measuringand determining the limit of noise [eve~ and the resultingproblems.